2016
DOI: 10.3324/haematol.2016.142471
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of thrombosis by neutrophils and extracellular nucleosome networks

Abstract: © Ferrata Storti FoundationActivation of intravascular blood coagulation and the formation of thrombi in microvessels (microvascular thrombosis) under certain conditions support a distinct mechanism of intravascular immunity named immunothrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 78 publications
(94 reference statements)
0
104
0
1
Order By: Relevance
“…Another potential mechanism could be the NET-induced activation of both the extrinsic and contact pathway of blood coagulation. 35,36 In our cohort, the higher NLR group showed a trend for higher fibrinogen accumulation in peripheral. A recent study found that patients with elevated neutrophil counts had a lower risk of hematoma expansion following acute ICH, 37 may also be explained by the increased coagulation by neutrophils.…”
Section: P-valuementioning
confidence: 51%
See 3 more Smart Citations
“…Another potential mechanism could be the NET-induced activation of both the extrinsic and contact pathway of blood coagulation. 35,36 In our cohort, the higher NLR group showed a trend for higher fibrinogen accumulation in peripheral. A recent study found that patients with elevated neutrophil counts had a lower risk of hematoma expansion following acute ICH, 37 may also be explained by the increased coagulation by neutrophils.…”
Section: P-valuementioning
confidence: 51%
“…Neutrophils originated from the blood circulating could be found within the brain as early as 4 hours in mice ICH models . And the results from the literature suggest that neutrophils could externalize decondensed nucleosomes and granule proteins to form neutrophil extracelluar traps (NETs) in some cases . In this context, with the pre‐existing cerebral microangiopathy in ICH, elevated NLR was prone to have NET increasing and thus led to microvascular thrombosis.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The process of NET release, or ‘NETosis’, was first characterised as a ‘last‐ditch’ neutrophil response to the presence of bacteria in the bloodstream (Brinkmann et al , ). NETosis represents a complex antibacterial response in which neutrophils release their nuclear contents, often in the process of dying, to capture and immobilise bacteria and other toxins in the bloodstream (McDonald et al , ; Kimball et al , ; Pfeiler et al , ). However, NET formation is also toxic to the surrounding vasculature and collateral endothelial injury from NETs is strongly associated with vascular dysfunction (Xu et al , ).…”
Section: How Do Circulating Blood Cells Contribute To Vte Development?mentioning
confidence: 99%